Analysis of the Application of Learning Models in Increasing Learning Motivation - Mazidah Hilmi Sa’diyah; Yuyun Bahtiar; Emi Lilowati; Nur Khasibah; Zilda Pangestu (SCHOOLAR: Social and Literature Study in Education, 2026)
One of the key elements in education is student learning motivation. Learning motivation is an important factor influencing student success in the learning process. This study aims to examine the application of the Team Games Tournament learning model in improving student learning motivation in Islamic Religious Education subjects. This study used a descriptive qualitative approach, with data collection through interviews, observations, questionnaires, and documentation. The results showed that the Team Games Tournament model was effective in increasing student learning motivation, as seen from increased student participation, enthusiasm, and enjoyment during learning. Students became more motivated because the learning process was presented in a fun, challenging way, and actively involved all group members. However, several challenges were identified, such as students' unpreparedness in facing competitive situations and diverse academic abilities within the group. Therefore, the Team Games Tournament model is effective in improving student learning motivation, especially when implemented with strategies that consider students' mental and academic readiness. It is hoped that this study can serve as a reference and basis for further research with a focus on improving the implementation of the Team Games Tournament model more optimally, such as developing tournament variations that are friendly to anxious students, and integrating Team Games Tournament with other learning models for different subjects.